Value of archival statistics in international archives management. Issue 1 (June 2020) - Schmerbauch, Maik
Abstract : This article is based on the author's professional experience. It discusses the generally unknown theme of the need for and value of professional archival statistics in international archives, exemplified on the operational statistics of an archive of an organization of the United Nations. The article points out the need for statistics to manage and monitor all archival operations efficiently. It proposes a scheme of required metadata and it discusses arguments for and against the tracking of archival statistics. The article delivers a range of recommendations for the implementation of statistics in archives.